Zataria multiflora and Pioglitazone Affect Systemic Inflammation and Oxidative Stress Induced by Inhaled Paraquat in Rats - Fatemeh Amin; Arghavan Memarzia; Ali Roohbakhsh; Farzaneh Shakeri; Mohammad Hossein Boskabady (Mediators of Inflammation)
The effects of Zataria multiflora (Z. multiflora) and pioglitazone (a PPAR-γ agonist) alone and in combination, on systemic inflammation and oxidative stress induced by inhaled paraquat (PQ) as a herbicide, which induced inflammation in rats, were examined. Rats were exposed to (1) saline (control) and (2) 54 mg/m3 PQ aerosols (8 times, every other day, each time for 30 min) without treatment or treated with (3 and 4) two doses of Z. multiflora (200 and 800 mg/kg/day), (5 and 6) two doses of pioglitazone (5 and 10 mg/kg/day), (7) low doses of Z.multiflora+pioglitazone, (Pio-5+Z-200 mg/kg/day) or (8) dexamethasone (0.03 mg/kg/day) for 16 days, after the last PQ exposure. Different variables were measured at the end of the treatment period. Exposure to PQ significantly increased total and differential white blood cells (WBC) counts, serum levels of nitrite (NO2), malondialdehyde (MDA), interleukin- (IL) 17, and tumor necrosis factor alpha (TNF-α), but reduced thiol, superoxide dismutase (SOD), catalase (CAT), IL-10, and interferon-gamma (INF-γ) (p<0.05 to p<0.001). Most measured parameters were significantly improved in groups treated with either doses of the extract, pioglitazone, Pio-5+Z-200 mg/kg/day, or dexamethasone compared to the PQ group (p<0.05 to p<0.001). The combination of low doses of Pio-5+Z-200 mg/kg/day showed significantly higher effects compared to each one alone (p<0.05 to p<0.001). Systemic oxidative stress and inflammation due to inhaled PQ were improved by Z. multiflora and pioglitazone. Higher effects of Pio-5+Z-200 mg/kg/day compared to each one alone suggest modulation of PPAR-γ receptors by the plant extract, but further studies using PPAR-γ antagonists need to be done in this regard.